1985
DOI: 10.1016/s0735-1097(85)80437-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure-controlled intermittent coronary sinus occlusion on regional ischemic myocardial function

Abstract: Pressure-controlled intermittent coronary sinus occlusion has been reported to reduce infarct size in dogs with coronary artery occlusion, possibly because of increased ischemic zone perfusion and washout of toxic metabolites. The influence of this intervention on regional myocardial function was investigated in open and closed chest dogs. In six open chest dogs with severe stenosis of the left anterior descending coronary artery and subsequent total occlusion, a 10 minute application of intermittent coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Our method was used to study the possible favorable mechanism of intermittent coronary sinus occlusion (43). During periodic occlusion of the coronary sinus the arterio-venous density gradient reversed, thus indicating washout of interstitial fluid from the myocardium (30,31,32,43).…”
Section: Arterio-venous Difference and Lymph Productionmentioning
confidence: 99%
“…Our method was used to study the possible favorable mechanism of intermittent coronary sinus occlusion (43). During periodic occlusion of the coronary sinus the arterio-venous density gradient reversed, thus indicating washout of interstitial fluid from the myocardium (30,31,32,43).…”
Section: Arterio-venous Difference and Lymph Productionmentioning
confidence: 99%
“…After the results of studies on coronary sinus blood density during ICSO treatment, Mohl et al 18 suggested indeed that the rapid reduction of coronary sinus pressure after the prolonged phase of plateau may induce a sort of aspirating effect on fluids and toxic metabolites accumulated in the ischaemic segment. In this way, PICSO would not just allow, but would improve the systolic cardiac venous drainage.…”
Section: Techniques For Csimentioning
confidence: 99%
“…Therefore, redistribution of venous flow together with periodic washout of metabolites, rather than additional arterial infusion and perfusion, is responsible for myocardial salvage [50,54,55].…”
Section: The Salvage Potential Of Picsomentioning
confidence: 99%